Dental-Derived Mesenchymal Stem Cells: State of the Art - Li, Bo; Ouchi, Takehito; Cao, Yubin; Zhao, Zhihe; Men, Yi (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem cells (MSCs) could be identified in mammalian teeth. Currently, dental derived MSCs (DMSCs) become a collective term for all the MSCs isolated from dental pulp, periodontal ligament, dental follicle, apical papilla, and even gingiva. These DMSCs possess similar multipotent potential as bone marrow derived MSCs, including differentiation into cells that have the characteristics of odontoblasts, cementoblasts, osteoblasts, chondrocytes, myocytes, epithelial cells, neural cells, hepatocytes, and adipocytes. Besides, DMSCs also have powerful immunomodulatory functions which enable them to orchestrate the surrounding immune microenvironment. These properties enable DMSCs a promising approach in injury repair, tissue regeneration, and treatments of various diseases. This review outlines the most recent advances in DMSCs’ functions and applications and enlightens how these advances are paving the path for DMSC-based therapies.